Bispidine Platform as a Tool for Studying Amide Configuration Stability - Krut’ko, Dmitry P.; Medved’ko, Alexey V.; Lyssenko, Konstantin A.; Churakov, Andrei V.; Dalinger, Alexander I.; Kalinin, Mikhail A.; Gudovannyy, Alexey O.; Ponomarev, Konstantin Y.; Suslov, Eugeny V.; Vatsadze, Sergey Z. (Molecules (Basel, Switzerland), 2022)
In this work, the solution conformations of seventeen 3,7-diacyl bispidines were studied by means of NMR spectroscopy including VT NMR experiments. The acyl groups included alkyl, alkenyl, aryl, hetaryl, and ferrocene moieties. The presence of syn/anti-isomers and their ratios were estimated, and some reasons explaining experimental facts were formulated. In particular, all aliphatic and heterocyclic units in the acylic R(CO) fragments led to an increased content of the syn-form in DMSO-d6 solutions. In contrast, only the anti-form was detected in DMSO-d6 and CDCl3 in the case when R = Ph, ferrocenyl, (R)-myrtenyl. In the case of a chiral compound derived from the natural terpene myrtene, a new dynamic process was found in addition to the expected inversion around the amide N-C(O) bond. Here, rotation around the CO-C=C bond in the acylic R fragment was detected, and its energy was estimated. For this compound, ΔG for amide N-C(O) inversion was found to be equal to 15.0 ± 0.2 kcal/mol, and for the rotation around the N(CO)–C2′ bond, it was equal to 15.6 ± 0.3 kcal/mol. NMR analysis of the chiral bispidine-based bis-amide was conducted for the first time. Two X-ray structures are reported. For the first time, the unique syn-form was found in the crystal of an acyclic bispidine-based bis-amide. Quantum chemical calculations revealed the unexpected mechanism for amide bond inversion. It was found that the reaction does not proceed as direct N-C(O) bond inversion in the double-chair (CC) conformation but rather requires the conformational transformation into the chair–boat (CB) form first. The amide bond inversion in the latter requires less energy than in the CC form.